Mosque as a Model of Learning Principles of Sustainable Architecture - Adi, Swambodo Murdariatmo; Puspitasari, Cynthia (Journal of Islamic Architecture, 2016)
The mosque is an integral part of the circuit-worship rituals of Islam. For Muslims in Indonesia, the role of the mosque as a place of worship, examines religion and some other activities occupy a strategic position not only as a religious symbol but more emphasis on the function of the space as a public building. Utilization of space in public buildings as well as space-ritual-social space will have meaning for the people in view of adaptation space used. Awareness of the importance of effective space utilization and management of water resources wisely in support of the ritual apply the principles of sustainable architecture will have a positive impact for the people to give directions as to how the principle of austerity-not wasteful in Islam can be applied. This paper will discuss about the process of continuous learning from the essence of understanding of the mosque as a model in implementing the process of life, taking into account the principles of simplicity, functional and wisdom, especially in the efficiency of utilization of local resources. The method used in this research is qualitative descriptive, which is explained the theory and based on literature and accompanied by case study that have implemented the principles. The output of this application of the principles of sustainable architecture in the planning and use of mosques as a place in the relationship with God and with fellow human relations can be a model for the faithful to deal with wisely challenge natural resource constraints, especially for future generations.